Comparative Study between Oral Hypoglycemic Drugs Repaglinide, Glibenclamide and Rosiglitazone on Some Biochemical Parameters in Type 2 Diabetic Patients - Kader, Sardar; J.Al-Shamma, Kassim; A. Majeed, Ibrahim; T. Al-Ani, Abdulla (Iraqi Journal of Pharmaceutical Sciences, 2017)
Type 2 diabetes mellitus is often characterized by hyperglycemia as a result of increased insulin resistance in hepatic/peripheral tissues and pancreactic B-cell dysfunction. Approximately 92% of patients with type 2 diabetes mellitus demonstrate insulin resistance, however hyperglycemia is always a consequence of insulin deficiency. This study was done on 120 patients newly diagnosed diabetes type 2 characterized by dyslipidemia that is increased triglycerides and decreased HDL. Hypoglycemia and weight gain are common problem with oral sulfonyl urea drugs. In this work three different oral hypoglycemic drugs repaglinide and glibenclamide (insulin secretagogues) and rosiglitazone (insulin sensitizer) were used for treatment of patients with type 2 diabetes mellitus. The effect of these drugs on fasting and postprandial blood glucose levels, lipid profiles, alanine aminotransferase and serum creatinine were studied.Three groups of newly diagnosed type 2 diabetic patients ,group 1 (40 patients) were subjected to treatment with repaglinide (2 mg three time daily) ,group 2(45 patients) were subjected to treatment with glibenclamide (5 mg once daily) ,group 3,(35 patients) were subjected to treatment with rosiglitazone (4 mg twice daily) . Fasting and postprandial blood glucose levels, lipid profiles (TC, TG, HDL and atherogenic index), alanine aminotransferase and serum creatinine were analyzed for these patients before and 4 and 8 weeks after oral hypoglycemic drug treatment. The same parameters were recorded for 40 normal individuals as control.The results demonstrated that repaglinide has a greater postprandial glucose regulator effect than glibenclamide and rosiglitazone. In addition the hypoglycemic episode and weight gain were less in patients treated with repaglinide than those treated with glibenclamide. Repaglinide produces greater percent reduction with respect to fasting blood glucose levels, postprandial blood glucose levels and atherogenic index compared to glibenclamide and rosiglitazone. Key words: oral hypoglycemic, repaglinide, glibenclamide, rosiglitazone.